Electrophoretic deposition: Novel in situ film growth mechanism of carbon nanocomposite films within non-conductive fabrics for multi-scale hybrid composites. (10th November 2020) - Sung, Dae Han; Doshi, Sagar M.; Murray, Colleen; Rider, Andrew N.; Thostenson, Erik T.
Abstract: A novel electrophoretic deposition (EPD) technique is developed to create uniform coatings of functionalized carbon nanotubes (CNTs) on non-conductive fabrics. EPD enables the creation of porous CNT composite films not just on the outer surface of the fabrics but onto individual fibers within fiber bundles or woven fabrics. This process can be conducted at room temperature without using any hazardous chemicals, making it inherently scalable, and can be applied to a wide range of fibers and textile structures to fabricate mechanically reinforced or multifunctional composites. A key advantage of EPD is the ability to control the CNT film thickness and microstructure because of the unique in situ film formation mechanism and by varying the process parameters. Unlike the mechanism for conductive carbon fibers, results for glass fibers suggest that positively charged nanotubes are destabilized by a local pH gradient and precipitate onto the negative electrode, which is followed by CNT film growth onto the fibers in direct contact with the electrode. Intimate contact is critical for both film extension from the electrode to fiber and throughout the filaments in a fabric. The electrically conductive CNT film acts as an extension of the electrode, promoting deposition throughout the fabric. Our model system studies aqueous dispersions of multi-walled CNTs functionalized with polyethyleneimine (PEI) deposited onto glass fibers. Key experiments are designed at different length scales, from single filaments to macroscopic composite rods, to visualize the film formation. Graphical abstract: Image 1